Landscape use of protected areas in the Hódmezővásárhely micro-region - Kis, Krisztián (Acta Agraria Debreceniensis, 2009)
One of the biggest questions of developing rural areas is that people and organisations living and making their activity there how and in what measure utilize the local or obtainable external resources. The concept of the landscape expresses the direct connection of the natural resources with the socio-economic processes. This is a two-way connection, (1) on the one hand the single landscapes provide the unique combination of natural conditions for the socio-economic utilisation which is different from other landscapes, (2) on the other hand as the result of the interaction of natural spheres together with the social and economic spheres the landscapes change in a different manner and in a different measure. The landscape as a territorial unit and as a resource is inseparable from the natural resources, and the nature conservation plays an increasingly important role in the use of the landscape and landscape management, which is an essential task not only in protected areas, but everywhere. The natural resources, the landscape, the nature conservation and the landscape use are related tightly, in which the so-called ecological/biological resources and their sustainable use have a significant role.